2018
DOI: 10.1111/1755-5922.12461
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene transfer therapy for coronary artery disease: A systematic review and meta‐analysis

Abstract: Vascular endothelial growth factor gene therapy appears to be safe and effective regarding serious cardiac events, with greater benefit when using adenoviral vectors. This meta-analysis highlights the need for further exploration in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Other studies showed that miR-214/361-5p were able to suppress VEGF expression and endothelial progenitor cell angiogenic activity [ 67 , 68 ]. Moreover, VEGF gene therapy is one of the safe and effective treatments in case of a cardiac event [ 69 ]. Furthermore, atorvastatin is one of the treatments for dyslipidemia and has been demonstrated to prevent cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that miR-214/361-5p were able to suppress VEGF expression and endothelial progenitor cell angiogenic activity [ 67 , 68 ]. Moreover, VEGF gene therapy is one of the safe and effective treatments in case of a cardiac event [ 69 ]. Furthermore, atorvastatin is one of the treatments for dyslipidemia and has been demonstrated to prevent cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…11 Early-stage clinical trials of VEGF gene transfer in patients with nonrevascularizable, severe CAD, and/or severe angina have demonstrated a favorable safety profile, with several trials demonstrating improvements in myocardial perfusion and anginal symptoms. 11,70 However, there was significant heterogeneity between trials, including critical differences in method of administration and vectors used for gene transfer. Experience gained from these initial trials and additional preclinical research has greatly increased our understanding of gene therapy pharmacokinetics and the biological mechanisms of angiogenesis.…”
Section: Recent Developments In Angiogenic Therapymentioning
confidence: 99%
“…In addition, numerous clinical trials over 2 decades have demonstrated a uniformly favorable safety profile for these techniques. 70,[79][80][81][82] Continued preclinical research has also advanced our understanding of the molecular mechanisms of angiogenesis to further refine therapeutic applications of the VEGF gene family. The VEGF-A gene undergoes extensive alternative splicing, forming multiple isoforms with distinct biological properties.…”
Section: Recent Developments In Angiogenic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models of cardiac gene therapy by using intracellular plasmid delivery suggested benefits of such approaches, as adenoviral delivery of vascular endothelial growth factor (VEGF) increased myocardial perfusion in a porcine ischemic myocardium ( Hassinen et al, 2016 ). However, similar to cell-based clinical trials, cardiac gene therapy did not yet lead to a breakthrough in the treatment of chronic ischemic human heart ( Yuan et al, 2018 ). To achieve clinically relevant success, timing of delivery, type and source of genes for cardiac therapy, furthermore, tracking methods need to be optimized ( Grochot-Przeczek, Dulak, and Jozkowicz 2013 ; Scarfe et al, 2017 ; Tompkins et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%